2002
DOI: 10.1006/viro.2002.1568
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of the Complete Genome of 18 Norwalk-like Viruses

Abstract: "Norwalk-like viruses" (NLV), a member of the family Caliciviridae, are the major causative agents of acute gastroenteritis and are genetically divided into two groups, genogroup I (GI) and genogroup II (GII). We have determined the complete nucleotide sequences of 10 new NLV strains. Using this information together with eight known NLV sequences, the criteria to further classify genotypes of NLV were investigated. Validation of the topological error based on the bootstrap value and the branch length (distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
281
1
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(297 citation statements)
references
References 52 publications
11
281
1
4
Order By: Relevance
“…Genetic classification of these viruses based on phylogenetic analysis of the complete capsid sequences is the generally accepted method [46,48,49]. Katayama et al [48] investigated which region of the genome was most suitable to classify the genotypes and genogroups of NoVs based on similarity plot analysis, bootstrap value and pairwise distances of the entire genomes of 18 strains, the complete sequences of ORF1, ORF2 and ORF3, and segments of ORF1 and ORF2. They found that the full-length genome, the complete ORF1 or ORF2, and the capsid Nterminal/S domain could segregate viruses into genus, genogroup and genotypes (also called genetic clusters).…”
Section: Genetic Organization and Classification Of Novs And Savsmentioning
confidence: 99%
See 3 more Smart Citations
“…Genetic classification of these viruses based on phylogenetic analysis of the complete capsid sequences is the generally accepted method [46,48,49]. Katayama et al [48] investigated which region of the genome was most suitable to classify the genotypes and genogroups of NoVs based on similarity plot analysis, bootstrap value and pairwise distances of the entire genomes of 18 strains, the complete sequences of ORF1, ORF2 and ORF3, and segments of ORF1 and ORF2. They found that the full-length genome, the complete ORF1 or ORF2, and the capsid Nterminal/S domain could segregate viruses into genus, genogroup and genotypes (also called genetic clusters).…”
Section: Genetic Organization and Classification Of Novs And Savsmentioning
confidence: 99%
“…The RdRp-capsid junction region of caliciviruses contains a highly conserved ~20 nucleotide (nt) motif in genomic and subgenomic RNA molecules that is suggested to be a transcription start signal [1,48]. This conserved nucleotide motif is almost identical within each genogroup of NoVs and SaVs, probably facilitating homologous recombination during co-infection of a cell by different genotypes of NoVs or SaVs within the same genogroup.…”
Section: Recombination Of Porcine Novs and Savsmentioning
confidence: 99%
See 2 more Smart Citations
“…A large selection of primers are available currently and these are able to amplify the most of genetic variants arising from the accumulation of point mutations associated with genetic recombination events. Most of the investigators have chosen primers for conserved regions, such the RdRp gene, in order to detect the greatest number of different strains [Jiang et al, 1990[Jiang et al, , 1993Ando et al, 2000;Katayama et al, 2002;Vinjé et al, 2004] but not all sequences can be accurately classified into the proper clusters by phylogenetic analyses [Zheng et al, 2006]; however, GII.4 variants were observed after the molecular analysis of the ORF1 region [Marshall and Bruggink, 2011]. During the last years it highlights a lack of reported data about sequence analyses of RdRp region that could suggest the use of this approach in addition to the VP1 capsid protein study chosen by the major networks of NoV surveillance [Park et al, 2011].…”
Section: Characterization Of the Outbreak In Ballshmentioning
confidence: 99%